2020
DOI: 10.6007/ijarbss/v10-i6/7276
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Orientation and Delinquent Behavioral Change: A Case Study of Ex-Juvenile Entrepreneurs in Katsina State, Nigeria

Abstract: Contemporary Entrepreneurship argument discovered the importance and the positive influence of autonomous orientation as one of the Entrepreneurial orientations (EO) towards organizational performance and profitability. However, discussion of autonomous orientation in the context of individuals such as entrepreneurs behavioral change influence still silent, especially in the context of ex-juvenile entrepreneurs that can give an insight into the Entrepreneurship body of knowledge. Therefore, the purposes of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, individuals with an innovation orientation can overcome obstacles and encourage their enterprises to adopt new processes, products and systems [79]. Individuals with higher entrepreneurial orientation tend to act innovatively [80], so enterprises are required to provide a creative atmosphere. This creative atmosphere encourages employees to act creatively and innovatively [4].…”
Section: Geo and Gimentioning
confidence: 99%
“…Furthermore, individuals with an innovation orientation can overcome obstacles and encourage their enterprises to adopt new processes, products and systems [79]. Individuals with higher entrepreneurial orientation tend to act innovatively [80], so enterprises are required to provide a creative atmosphere. This creative atmosphere encourages employees to act creatively and innovatively [4].…”
Section: Geo and Gimentioning
confidence: 99%
“…Innovativeness was defined by Miller [32] as the propensity to engage in creativity and experimentation through the introduction of new goods or services. Furthermore, innovation is the ability to recognize and participate in business activities in creative and unusual ways [59]. Innovativeness is concerned with fostering and encouraging new ideas, experimentation, and creativity that will lead to the development of new services, products, or processes.…”
Section: Defining the Study Constructsmentioning
confidence: 99%
“…The results also showed that Micro enterprises are less proactive and preferred to be followers rather than leaders, they are also risk averse. Despite of these studies, none have focused on single EO dimension except in Nigeria Usman, and Hashim, (2020) who explored that, autonomous orientation behaviors have a positive influence on ex-juvenile entrepreneurs' delinquent behavioral change. Still not explored ex-juvenile innovativeness orientation behaviors influence.…”
Section: Entrepreneurial Orientation Theory: Innovation Orientation and Proposition Developmentmentioning
confidence: 99%